UHPLC-QQQ-MS/MS method for the simultaneous quantification of 18 amino acids in various meats - Wang, Mengxian; Guo, Junxiu; Lin, Huimin; Zou, Dawei; Zhu, Jiaxuan; Yang, Zhenyuan; Huang, Yufeng; He, Fan (Frontiers in Nutrition, 2024)
Amino acids are an essential source of human protein, and their content and composition are the main factors determining food protein utilization rate. Determining amino acids is essential in the component analysis of food. Therefore, a groundbreaking technique was developed utilizing ultrahigh performance liquid chromatography interfaced with a triple quadrupole mass spectrometer (UHPLC-QQQ-MS/MS) for concurrently quantifying eighteen amino acids across various types of meat. According to the test results, it can be known that the average content of glutamate (2.03×10 4 ± 3.94 ×10 3 μg/g in pig feet) was the highest in all meat samples, and the content of aspartate (0.0945 ± 0.0950 μg/g in pork) was the lowest, which was not detected in some samples such as beef and lean meat. Orthogonal partial least-squares discrimination analysis (OPLS-DA) showed: 1) thirteen amino acids (arginine, valine, serine, alanine, lysine, glycine, asparagine, methionine, proline, threonine, glutamate, phenylalanine, and leucine, VIP > 1) were used as characteristic amino acids between pork and pig feet；2) serine, threonine, alanine, histidine, asparagine, and arginine (VIP > 1) were used as signature amino acids in different components of pork (lean meat, fat, and pigskin); 3) asparagine, glutamate, histidine, tyrosine, and valine (VIP > 1) were considered as signature amino acids in different types of meats (pork, mutton, beef, and chicken). This study provides a new UHPLC-QQQ-MS/MS method for the determination of amino acid content in meat and also provides data support for the comprehensive evaluation of the nutritional value of foods containing amino acids.